2011
DOI: 10.17659/01.2011.0003
|View full text |Cite
|
Sign up to set email alerts
|

Sternal Tuberculosis: An Uncommon Presentation

Abstract: Skeletal tuberculosis as an extrapulmonary entity is uncommon accounting for less than 7% cases [1]. Tubercular involvement of the sternum is rarer even in countries where tuberculosis is highly prevalent [2]. We herein report an unusual case of tuberculous osteomyelitis of sternum with acute presentation as a swelling over anterior chest wall.An eleven year old girl presented with one week history of chest pain and swelling over anterior chest wall. There was history of progressive weight loss and low grade i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 10 publications
(4 reference statements)
0
10
0
Order By: Relevance
“…As a result, 76 articles[ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 ] were obtained, including 56 (73.7%) case reports,[ 1 3 4 5…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As a result, 76 articles[ 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 ] were obtained, including 56 (73.7%) case reports,[ 1 3 4 5…”
Section: Resultsmentioning
confidence: 99%
“…A total of 107 (67.3%) cases were primary,[ 2 5 9 10 13 14 16 17 18 19 21 22 23 28 30 31 32 33 34 38 39 40 42 43 44 48 50 52 53 56 59 60 61 62 64 65 66 67 69 70 72 73 74 75 76 ] 33 (20.8%) were secondary,[ 6 11 12 15 20 24 25 26 29 35 37 46 47 51 55 62 64 66 67 ] and 19 (11.9%) were postoperative. [ 1 3 4 7 8 27 36 41 45 49 54 58 62 63 68 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies by few authors have found extrasternal involvement presenting as bilateral pleural effusion or as involvement of other organs. [6][7][8][9][10][11][12][13][14][15][16] As per WHO guidelines if an individual is diagnosed to have HIV infection then it is recommended to start screening for tuberculosis before starting antiretroviral therapy and also to continue screening at regular intervals and vice versa. The various screening and surveillance tools are focused towards symptoms of cough, night sweats and weight loss.…”
mentioning
confidence: 99%
“…While with the availability of gene expert it is not necessary. 16 While testing by Interferon gamma release assay also known as QuantiFERON-TB Gold there is limitation of inability to differentiate between active and latent infection. 19,20 Isolated case reports suggest estimation of vitamin D levels which were found to be low in their study but the rationale of conducting the test being unclear.…”
mentioning
confidence: 99%